Light and dissolved phosphorus interactively affect microbial metabolism, stoichiometry and decomposition of leaf litter. (1st April 2016) - Halvorson, Halvor M.; Scott, Erin E.; Entrekin, Sally A.; Evans‐White, Michelle A.; Scott, J. Thad
Summary: In aquatic settings, light can stimulate algal growth to affect microbial transformation of organic substrates. These effects may depend on dissolved nutrients that differentially constrain microbial autotrophy and heterotrophy to drive contrasting carbon (C) and phosphorus (P) dynamics during decomposition. We incubated sugar maple ( Acer saccharum ) litter under three dissolved P amendments (0, 50 or 500 μg L −1 P) and two light levels (14 or 475 μmol photons m −2  s −1 ) in laboratory microcosms. We measured litter chlorophyll a, microbial respiration and net metabolism, carbon:nitrogen (C:N) and C:P content, microbial P uptake and release and litter decomposition over 134 days. Elevated dissolved P increased algal biomass in the high‐light treatment and magnified net heterotrophy and autotrophy in the low‐ and high‐light treatments, respectively. Litter C:P and C:N declined as dissolved P increased, and litter C:P was further reduced by high light only in the highest P treatment. Microbial P uptake fluxes peaked under moderate P and high light, whereas P release fluxes were consistently low throughout the experiment. The percent of P uptake that was released was significantly higher under low light. High light stimulated decomposition under low P but slowed decomposition under high P, suggesting increased nutrients weakened algal priming of litter decomposition. Our study suggests factors controlling the degree of autotrophy versus heterotrophy on organic matter, such as light and nutrient availability, may interactively shift litter C and P dynamics during decomposition.